Análise crítica do discurso quilombola em Conceição das Crioulas: oralidade, memória e identidade social. - França, Aurênia Pereira de (2018)
The current investigation reflects discursive aspects within the ethnical relations and their af-firmation, sustenance, collective memory maintenance and identity processes in the quilombola community of Conceição das Crioulas in Salgueiro, in the hinterland of Pernambuco. Under the theme: “Critical Analysis of the quilombola Discourse in Conceição das Crioulas: Orality, memory and social identity”. Its general objective is Analyzing quilombolas discourses from its memory and orality whilst practice of ethnical identity legitimization. Thereby, in order to achieve the specific objectives of this research, it was stablished: a) Interpreting subjects’ dis-courses about the condition of being quilombola; b) Comprehending the discursive practices present in mythic and historic narratives related to the organization of the quilombola ethnical identity, and c) Observing the usage of telling stories in the daily life of quilombolas from Conceição das Crioulas. It’s about a qualitative, transversal, analytical research methodology with ethnomethodological approach, featuring an important interface between anthropology and linguistics. It’s important to highlight that this research is based on Fairclough’s Social discourse Theory (2001, 2016) and its tridimensional Discourse Critical Analysis model – ACD, when it proposes examining the language role in the reproduction of social practices as well as ideologies in social transformation. It considers a side’s discourse affectionate to social structure, and, on the other hand, constituent of this same structure, enabling it to extend its effects over the subjects and their identities, social relationships, knowledge and beliefs. We also used Van Dijk’s Discourse Critical Analysis (ACD) in a perspective of discursive analysis which incorporates different disciplines in the study of the way the social structures of power and domination are instituted, reproduced and suffer resistance by means of the language using theoretical and methodological mechanisms offered by ACD to analyze the reproduction of racism in the society by means of discourse, under Van Dijk’s sociocognitive perspective ( 2010; 2012). Stuart Hall (2003,2006) who discusses the suppositions of identity and culture, and Pollak (1989, 1992) who discusses memory and social identity among others, are also the-oretical references. This research aims at noticing how the quilombola community of Con-ceição das Crioulas resists through time and keeps itself alive, reframing its people’s history despite contemporaneity.This black, rural community was founded by six black women who fought for possessing land, politics and ethnical rights in the perspective of affirming their iden-tities, nourished by discursive memories aiming at fighting racism and discrimination.